Composite magnesium phosphate coatings for improved corrosion resistance of magnesium AZ31 alloy. (December 2016) - Jayaraj, Jithu; Amruth Raj, S.; Srinivasan, A.; Ananthakumar, S.; Pillai, U.T.S.; Dhaipule, Nanda Gopala Krishna; Mudali, U. Kamachi
Graphical abstract: Highlights: A composite coating of struvite and newberyite on AZ31 alloy was obtained. Effect of pH (4.5–7.5) of the coating bath on corrosion resistance was investigated. Highest corrosion resistance was obtained at coating bath pH of 7.5. Uniform coating with more struvite improved the corrosion performance at pH 7.5. Abstract: Corrosion performance of magnesium phosphate composite coatings consisted of struvite (MgNH4 PO4 ·6H2 O) and newberyite (MgHPO4 ·3H2 O) on magnesium AZ31 alloy obtained in a high concentrated NH4 H2 PO4 phosphating bath at different pH ranges in 1 wt.% NaCl aqueous solution were analyzed using potentiodynamic polarization test, EIS analysis and immersion test. The test results revealed that the corrosion performance increased with increase in the coating bath pH which could be attributed to the uniform and dense magnesium phosphate coating with fewer defects and increase in the content of insoluble struvite phase.